NMR structure of the N-terminal domain of capsid protein from the mason-pfizer monkey virus - Macek, Pavel; Chmelík, Josef; Krízová, Ivana; Kaderávek, Pavel; Padrta, Petr; Zídek, Lukás; Wildová, Marcela; Hadravová, Romana; Chaloupková, Radka; Pichová, Iva; Ruml, Tomás; Rumlová, Michaela; et al. (Journal of molecular biology, 2009)
The high-resolution structure of the N-terminal domain (NTD) of the retroviral capsid protein (CA) of Mason-Pfizer monkey virus (M-PMV), a member of the betaretrovirus family, has been determined by NMR. The M-PMV NTD CA structure is similar to the other retroviral capsid structures and is characterized by a six alpha-helix bundle and an N-terminal beta-hairpin, stabilized by an interaction of highly conserved residues, Pro1 and Asp57. Since the role of the beta-hairpin has been shown to be critical for formation of infectious viral core, we also investigated the functional role of M-PMV beta-hairpin in two mutants (i.e., DeltaP1NTDCA and D57ANTDCA) where the salt bridge stabilizing the wild-type structure was disrupted. NMR data obtained for these mutants were compared with those obtained for the wild type. The main structural changes were observed within the beta-hairpin structure; within helices 2, 3, and 5; and in the loop connecting helices 2 and 3. This observation is supported by biochemical data showing different cleavage patterns of the wild-type and the mutated capsid-nucleocapsid fusion protein (CANC) by M-PMV protease. Despite these structural changes, the mutants with disrupted salt bridge are still able to assemble into immature, spherical particles. This confirms that the mutual interaction and topology within the beta-hairpin and helix 3 might correlate with the changes in interaction between immature and mature lattices.
Keywords: substituce aminokyselin; Models, Molecular; sekvenční delece; Capsid Proteins; terciární struktura proteinů; Mutant Proteins; Nuclear Magnetic Resonance, Biomolecular; molekulární modely; Sequence Deletion; nukleární magnetická rezonance biomolekulární; Amino Acid Substitution; Mason-Pfizer monkey virus; Protein Structure, Tertiary; Masonův-Pfizerův opičí virus; virové plášťové proteiny; mutantní proteiny